Development of integrated multitrophic aquaculture–based cage rearing system in an underutilized fishing port and its application in marine stock enhancement - Lee, Hung-Tai; Chang, Yung-Cheng; Liao, Cheng-Hsin; Hsu, Te-Hua (Frontiers in Marine Science, 2022)
Human activity and global climate change have severely affected marine ecosystems and fishery resources. Habitat conservation and stock enhancement are considered effective methods. Moreover, with the gradual disappearance of fishery resources, fishing ports have become underutilized spaces. Currently, 73 of the 221 fishing ports in Taiwan are underutilized. Therefore, we, for the first time, developed an integrated multitrophic aquaculture (IMTA)-based cage rearing system suitable for stock enhancement and applied it in an optimal underutilized fishing port after the site evaluation and selection of 17 potential fishing ports fishing. We further tested that hypothesis that hatchery-produced organisms can be reared and monitored appropriately in this cage rearing system with good survival and growth as well as less environmental impact and handling stress. Through the collocation of various release organisms of different trophic levels, the cage rearing system can reduce environmental impacts as evidenced by the steady water quality (stable pH and undetectable levels of ammonia nitrogen, nitrates, and nitrites). As for the fish welfare, this semiartificial rearing system could also reduce the discomforts of hatchery-produced organisms after transportation and facilitate their adaptations to the released environments as evidenced by positive growth and high survival rates (94%–98%). The cultured and naturally grown shellfish and algae on the cage nets could provide habitats for hatchery-produced and wild organisms that facilitate habitat conservation and stock enhancement. Taken together, we have demonstrated that it is feasible to implement this novel IMTA-based cage rearing system in an underutilized fishing port required for marine stock enhancement.